Tác động của giá cả cảm nhận, chất lượng giao hàng đến ý định mua hàng lặp lại trong thương mại điện tử - Phan Tấn, Lực (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The purpose of this study is to explore the role of perceived price, delivery quality in influencing the repeat purchase intention through perceived value and consumer satisfaction. A total of 791 survey questionnaires were collected by convenience sampling method from consumers who have previously purchased the same online store. This study uses partial least squares to analyze data through SmartPLS 3.0 software. The procedure for data analysis consists of the assessment of the reliability and validity of the measurement model and the evaluation of the structural model. The research results show that the role of delivery quality and perceived price affects perceived value and does not affect satisfaction, while perceived value directly affects repeat purchase intention and indirectly through satisfaction. Accordingly, the research results imply that the online stores should pay attention to order processing time, packaging time and cooperate with shipping companies to improve delivery quality. In addition, online stores should also have appropriate pricing policies to help increase perceived value and form repeat purchase intentions.